Smoke & mirrors : the Canadian tobacco war - Cunningham, Rob (International Development Research Centre, 1996)
Smoke & Mirrors provides an insider's view of the Canadian tobacco war, a hundred-year old conflict that began to escalate in the 1980s. Written by a prominent antismoking advocate, the book explains how Canada emerged as a global leader in the public health crusade to regulate the powerful tobacco industry. Author Rob Cunningham exposes the industry's deception and tactics; and describes in fascinating detail the bitter campaigns to maintain high tobacco taxes, ban tobacco advertising, eliminate tobacco sponsorships, require plain packaging, mandate clear health warnings, and prohibit smoking.